2022
DOI: 10.1002/adom.202200114
|View full text |Cite
|
Sign up to set email alerts
|

Laser Photochemical Nanostructuring of Silicon for Surface Enhanced Raman Spectroscopy

Abstract: In this work, a novel method of fabricating large‐area, low‐cost surface‐enhanced Raman spectroscopy (SERS) substrates is explained which yields nanostructured surface utilizing laser‐induced chemical etching of crystalline silicon (Si) in an hydrofluoric acid solution. Nanostructuring of Si surface is followed by deposition of a thin noble metal layer to complete the fabrication procedure. A 50 nm thick silver (Ag) layer is shown to maximize the SERS performance. The SERS effect is attributed to the electroma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…In our recent study, we showed that most enhanced Raman signals are observed from the substrates with dense etched surfaces and no significant signal is obtained from Ag on flat Si surfaces. [ 65 ]…”
Section: Resultsmentioning
confidence: 99%
“…In our recent study, we showed that most enhanced Raman signals are observed from the substrates with dense etched surfaces and no significant signal is obtained from Ag on flat Si surfaces. [ 65 ]…”
Section: Resultsmentioning
confidence: 99%
“…It can conduct a nondestructive analysis of the gas phase, the liquid phase, the aqueous phase, and the composition. [ 43 ] Raman spectroscopy detection is the most advanced method for inclusions composition analysis. Wang et al [ 44 ] indicated that Raman spectroscopy is a very effective tool for in situ mineral identification, which can complement the performance of existing spectral methods.…”
Section: Sensing and Imaging Modulementioning
confidence: 99%
“…However, the enhanced Raman effect of pure silicon is not as sensitive as that of precious metals; therefore, the synergistic effect of precious metals is needed [ 12 , 13 , 14 ]. It has previously been demonstrated that 3D structured silicon with a large specific surface area and controlled 3D structure can effectively increase the number of hot spots and further improve the sensitivity of SERS signals [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%